PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PLN (PERSERO) AREA PAYAKUMBUH - Mutiara Okselia Demus; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Problems in research is the atmosphere or work environment that is less comfortable that occurs during working hours. Where there are some late employees returning to work during the day after the end of the break, as well as employees returning home before business hours. This of course will affect the satisfaction of other employee's work as well as the task of the leader according to its area to create a comfortable atmosphere by eliminating the gap on job satisfaction itself. The purpose of this study is to determine the effect of transformational leadership and work environment on employee job satisfaction at PT. PLN (Persero) Payakumbuh Area.The method in this research is quantitative descriptive, using SPSS program to analyze the influence of each variable of transformational leadership and work environment to employee job satisfaction. In the sampling method used census, which is as much as 40 respondents or all employees at the office of PT. PLN (Persero) Payakumbuh area with data collection techniques through questionnaires.The result of research using multiple linear regression, correlation coefficient test (R) and coefficient of determination (R2), where it can be seen that transformation leadership has a significant effect on employee job satisfaction, work environment has significant effect on employee job satisfaction and transformational leadership and work environment significantly Employee job satisfaction.Keywords : Transformational Leadership, Work Environment, and Employee job Satisfaction.